Superformula-Based Compact UWB CPW-Fed-Patch Antenna With and Without Dual Frequency Notches - Amjad A. Omar; Shaimaa Naser; Mousa I. Hussein; Nihad I. Dib; Maram W. Rashad (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents two new designs of UWB coplanar waveguide (CPW)-fed-patch antennas operating in the FCC frequency band (3.1-10.6 GHz). The first design uses the superformula to produce a circular patch with sawtooth-like circumference. As compared to a regular circular patch antenna whose diameter is 25 mm, the proposed circular patch has a smaller diameter of 18.2 mm. Moreover, the proposed antenna covers the entire FCC band unlike a regular circular patch of the same radius. The second design introduces two frequency notches at 3.3-3.8 GHz (WiMAX) and 5-5.9 GHz (WLAN) using two arc shaped circular slots etched on the circular patch and a split-ring resonator (SRR) that is placed on the opposite side of the substrate. Measurements and simulations using HFSS show that the return loss is better than 10 dB across the band except at the two notch locations in Design II. Results are also presented for the radiation pattern and peak gain of both designs. Each of the proposed antennas has a compact size of 24 mm x 19 mm on a 1.5 mm Rogers Substrate (epsilon r=3.85).